Obesity and its implications on oncological urological surgery. Issue 5 (September 2017) - Abufaraj, Mohammad; Mari, Andrea; Mansy, Karim; Sievert, Karl-Dietrich
Abstract : Purpose of review: To review and summarize the contemporary knowledge of the implications of obesity on perioperative outcomes in oncological urologic surgeries. Recent findings: In men undergoing radical prostatectomy, obesity seems to confer a higher risk of intraoperative bleeding, biochemical recurrence, urinary incontinence, and postoperative erectile dysfunction. The literature was not consistent regarding the benefits of a minimally invasive approach in overweight and obese patients. Similarly, available data suggest a higher risk of complications in obese patients undergoing radical cystectomy. Obesity does not seem to confer a higher risk of morbidity in patients undergoing radical nephrectomy and nephroureterectomy. However, studies reported conflicting surgical outcomes in obese patients treated with partial nephrectomy. Overweight and obesity status are associated with higher morbidity in patients treated with inguinal lymph node dissection for penile cancer. No data are available regarding the impact of obesity in obese patients treated with retroperitoneal lymph node dissection for testicular cancer. Summary: Although randomized clinical data are lacking and the results of many studies are inconsistent, evidence supports the feasibility and safety of different oncological urological surgeries in obese patients. Nevertheless, obesity is an important comorbidity associated with a higher morbidity rate in most oncological urological surgeries.